Comparison of Agreement Statistics in Case of Multiple-Raters and Diagnostic Test Being Categorical: A Simulation Study (Annals of Medical Research, 2021)
None
Keywords: Fleiss Kappa; Gwet’s AC1 Statistics; Krippendorff Alpha; Agreement between Raters.